Situating east Indonesia's EFL Learners attitudes toward the extensive listening practices - Yosefina Rosdiana Su; Fatmawati Fatmawati; Stanislaus Guna; Fransiskus Jemadi; Yovita Narsi Mat; Ronaldus De'e (EduLite: Journal of English Education, Literature and Culture, 2021)
Learning English as a foreign language is very challenging for both teachers and students in Flores, East Nusa Tenggara of Indonesia. The challenges are primarily caused by their lack of exposure to the authentic environment of English. In dealing with this phenomenon, the appropriate listening practices expect to help the learners to obtain and construct their knowledge of English as well as to acquire more comprehensible input. This article reports an investigation on the EFL learners’ attitudes toward the extensive listening practices. It applied mixed-method research procedures involving 55 students of the English language and education program of Universitas Katolik Indonesia Santu Paulus Ruteng. The data were collected through a survey coupled with Focus Group Discussions with 15 participants. This research revealed that the learners' attitudes are identified into two main categories called positive and negative attitudes. In this case, 38 % of the participants have positive attitudes toward extensive listening practices and 62% of the participant reflected the negative attitude toward the extensive listening practices. Learners with a positive attitude had a very strong awareness of the significance of listening skills in L2 learning. To improve their listening skills, they develop their listening practices outside the classroom consistently. Meanwhile, learners with negative attitudes were categorized as dependent learners who practiced their listening skills during the listening course only. This group of learners was less aware of the significance of listening skills in L2 learning and their listening practices were highly dependent on the teachers' instruction. It showcased that both of the learners’ internal and external factors were strongly contributed to this poor extensive listening practices.  The EFL teachers are then strongly suggested to strengthen the learners’ awareness on the significance of Listening Skills in L2 learning as well as design more instructed extensive listening practices outside the classroom.